1991
DOI: 10.1080/17450399109428482
|View full text |Cite
|
Sign up to set email alerts
|

Purin- und Pyrimidinmetaboliten zur Beurteilung des Pansenstoffwechsels: HPLC-Analysen in Milch und Blutplasma

Abstract: In milk and blood plasma samples of 6 German Simmental and 12 German Black and White heifers it was investigated, whether purine and pyrimidine compounds are suitable indicators of the microbial protein synthesis in the rumen. Therefore the secreted quantities in milk and the concentration in blood plasma are correlated with energy intake. The results indicated significant correlation coefficients for both the secretion quantity of allantoin in milk (r = 0.942) and the concentration of allantoin in blood plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Urinary concentrations of pseudouridine (Table 1) were similar to the 2.2 mmol/day of the non-lactating cows measured by Puchala et al (1993); however, plasma pseudouridine concentrations were not in the range of Rosskopf et al (1991), who found 0.006 ± 0.0016 mmol L − 1 circulating in bovine blood plasma. The cattle used in the study of Rosskopf et al (1991) were milking cattle and not rapidly growing beef steers, and this may account for the discrepancy.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Urinary concentrations of pseudouridine (Table 1) were similar to the 2.2 mmol/day of the non-lactating cows measured by Puchala et al (1993); however, plasma pseudouridine concentrations were not in the range of Rosskopf et al (1991), who found 0.006 ± 0.0016 mmol L − 1 circulating in bovine blood plasma. The cattle used in the study of Rosskopf et al (1991) were milking cattle and not rapidly growing beef steers, and this may account for the discrepancy.…”
Section: Discussionsupporting
confidence: 47%
“…The cattle used in the study of Rosskopf et al (1991) were milking cattle and not rapidly growing beef steers, and this may account for the discrepancy.…”
Section: Discussionmentioning
confidence: 88%
“…VI) were rather low compared to values reported in the literature for lactating cows (370.6 ± 79.1 µmol . L -1 , [47]) or ovines (12.2 ± 3.5 mmol . d -1 , [51]).…”
Section: Rumen Microbial Growthmentioning
confidence: 99%
“…review by Shingfield [51]). Moreover, blood allantoin concentrations in cattle have been correlated with renal excretion of purine derivatives [11,24,47] and rumen microbial growth [55]. Hence, in our experiments, the effect of dietary treatment on duodenal microbial N supply has been evaluated from the renal excretion of purine derivatives (Exps.…”
Section: Rumen Microbial Growthmentioning
confidence: 99%
“…Die Ausscheidung erfolgt hauptsachlich iiber die Nieren. Gut mefibare Mengen von Allantoin sind auch in der Milch vorhanden (TIEMEYER et al, 1984;ROSSKOPF et al, 1991). Da die mikrobielle Synthese im Pansen mafigeblich von der Verfugbarkeit an verdaulicher Energie abhangt (MCALLAN et al, 1986) (WATTS, 1981).…”
unclassified